A Scalable Multi-Channel Software Potentiostat - Siegert, Michael (Frontiers in Energy Research, 2018)
Electronic hardware is a major cost driver when scaling bio-electrical systems (BES) for biological methanation. Many academic publications reporting BES experiments lack statistical power because such experiments are seldom carried out in replicates. One reason is that conventional electronic potentiostats often lack sufficient independent channels required for replication. Nonetheless, replication is necessary for any statistical analysis. Here, I developed a simple, easy-to-scale multi-channel software potentiostat which solves these problems. The software controls off-the-shelf hardware saving up to 80% of the hardware cost spent otherwise for electronic potentiostats. The difference between the setpoint and the measured working electrode potential was comparable to that of hardware potentiostats. Chronoamperomtric experiments were carried out in parallel for 10 days at +0.300 V and −0.800 V. A scaling experiment using a tubular wastewater treatment reactor demonstrated that the software can be used to scale BES. The results show that a simple proportional controller can replace expensive potentiostats for chronoamperometry.